Where islam and judaism join together : a perspective on reconciliation - Har-El, Shai.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Introducing a framework to generate new conversations about inter-religious dialogue and create a community of religions, Shai Har-El argues that Islam and Judaism, sister religions, are closely related to one another with roots intertwined in the land, in the language, and in the memories of shared history.
Keywords: Religion; Religions; Islam; Judaism; Religion -- History; Middle East -- Politics and government; Religion and sociology; Religious Studies; History of Religion; Sociology of Religion; Middle Eastern Politics; Comparative Religion